Thermally conductive silicone composition and method for producing same

By using a specific proportion of aluminum nitride powder and irregular zinc oxide powder in the thermally conductive material, combined with organopolysiloxane and alkoxysilane, the problem of deterioration of fluidity and workingability of thermally conductive materials after high volume filling is solved, and the efficient heat dissipation and durability reliability are improved.

CN119585364APending Publication Date: 2025-03-07SHIN ETSU CHEMICAL CO LTD

Patent Information

Application Number
CN202380055200.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-29
Filing Date
2023-07-11
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

After the existing thermally conductive materials are filled with a high amount of thermally conductive filler, their fluidity and working properties are deteriorated, and they cannot effectively dissipate heat, and their durability and reliability are poor under high temperature and high humidity conditions.

Method used

By using a specific ratio of (C) aluminum nitride powder and (D) irregular zinc oxide powder, combined with organopolysiloxane and alkoxysilane, a thermally conductive silicone composition is formed, ensuring that excellent fluidity and handling properties are maintained after high amounts of filler thermally conductive filler.

Benefits of technology

The durability and reliability of the thermally conductive silicone composition under high temperature and high humidity conditions is achieved, excellent fluidity and working properties are maintained, and efficient heat dissipation performance is ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005251053660000041
    Figure BDA0005251053660000041
  • Figure BDA0005251053660000061
    Figure BDA0005251053660000061
  • Figure BDA0005251053660000071
    Figure BDA0005251053660000071
Patent Text Reader

Abstract

Provided is a thermally conductive silicone composition. (A) an organopolysiloxane having a kinematic viscosity of 10-10000 mm2 / s, (B) an organopolysiloxane having a kinematic viscosity of 10-100000 mm2 / s, (C) an aluminum nitride powder having an oxygen content of 0.5 mass% or less, a BET specific surface area of 1.0 m2 / g or less, and an average particle diameter of 3-40 [mu] m, the ratio of coarse particles of 44-105 [mu] m in a volume-based laser diffraction particle size distribution being 10.0 mass% or less of the total component (C), and (D) Irregular zinc oxide powder: the blending ratio of component (C) and component (D) is 5.0: 5.0-9.5: 0.5, expressed by mass ratio, and the total powder amount of component (C) and component (D) is 70-85 vol% of the entire composition, the thermally conductive silicone composition maintains good flowability and handling properties, has excellent heat dissipation performance, and has excellent durability and reliability under high-temperature, high-temperature, high-humidity conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a thermally conductive silicone composition having excellent insulation and thermal conductivity and a method for producing the same. Background Art

[0002] Since most electronic components generate heat during use, it is necessary to remove the heat from the electronic components in order to properly function. In particular, integrated circuit components such as CPUs used in personal computers generate more heat due to the high-speed operation frequency, and the solution to deal with heat has become an important issue.

[0003] As a means of removing the heat, many methods have been proposed. In electronic components that generate a lot of heat, a method has been proposed to dissipate heat by placing a thermally conductive material such as a thermally conductive grease or a thermally conductive sheet between the electronic component and a member such as a heat sink. However, this method cannot dissipate heat in areas with greatly different thicknesses (see Patent Documents 1 and 2).

[0004] As such a thermally conductive material, a composition based on silicone oil and blended with zinc oxide and aluminum oxide powder is known, but the heat resistance at 200° C. is not satisfactory (see Patent Documents 3 and 4).

[0005] Furthermore, in order to improve thermal conductivity, as a thermal conductive material using aluminum nitride powder, the above-mentioned Patent Document 1 discloses a thermal conductive material composed of a liquid silicone carrier, silica fibers, and at least one selected from dendritic zinc oxide, flaky aluminum nitride, and flaky boron nitride. Patent Document 5 discloses a silicone grease composition obtained by blending spherical hexagonal aluminum nitride powder of a certain particle size range in a specific organopolysiloxane. Patent Document 6 discloses a thermal conductive silicone grease composed of a combination of aluminum nitride powder with a fine particle size and aluminum nitride powder with a coarse particle size. Patent Document 7 discloses a thermal conductive silicone grease composed of a combination of aluminum nitride powder and zinc oxide powder. Patent Document 8 discloses a thermal conductive grease composition using aluminum nitride powder surface-treated with organosilane, but it does not meet the requirements from the viewpoints of durability and reliability.

[0006] Patent document 9 discloses a thermally conductive polysiloxane composition using irregular aluminum nitride particles with an average particle size of 30 to 150 μm. The proportion of coarse particles is not specified. If multiple types of aluminum nitride with a wide particle size distribution are used, the filling property is poor and is insufficient to achieve the goal of high thermal conductivity. In addition, the heat-resistant properties are not satisfactory.

[0007] The thermal conductivity of aluminum nitride is 70 to 270 W / (m·K), while the thermal conductivity of diamond is higher, 900 to 2000 W / (m·K). Patent Document 10 discloses a thermally conductive silicone composition comprising a silicone resin, diamond, zinc oxide, and a dispersant, but the thermally conductive silicone composition does not satisfy the heat-resistant properties.

[0008] In addition, metals are materials with high thermal conductivity and can be used in places where insulation of electronic components is not required. Patent Document 11 discloses a thermally conductive grease composition obtained by mixing metal aluminum powder with a base oil such as silicone oil, but this composition does not meet the requirements because it has no insulating properties.

[0009] All thermally conductive materials and thermally conductive greases are currently insufficient for the heat generated by integrated circuit components such as CPUs.

[0010] As can be seen from the theoretical formula of Maxwell and Bragmann, the thermal conductivity of the material obtained by mixing a thermally conductive filler with silicone oil is almost independent of the thermal conductivity of the thermally conductive filler when the volume fraction of the thermally conductive filler is below 0.6. When the volume fraction exceeds 0.6, the influence on the thermal conductivity of the thermally conductive filler first appears. That is, when the thermal conductivity of thermally conductive grease is to be improved, first of all, it is important to fill a high amount of thermally conductive filler and how to use a filler with high thermal conductivity. However, by filling in a high amount, the fluidity of the thermally conductive grease is reduced, and the workability such as coating (dispensing, screen printing) is deteriorated, which has the problem of being unable to be used in practical use. In addition, due to the reduction in fluidity, there is a problem that it cannot follow the fine unevenness on the surface of electronic components and heat sinks, and the contact thermal resistance increases.

[0011] To date, in order to achieve a high filling amount and obtain a thermally conductive material with good fluidity, research has been conducted on the addition of an alkoxy-containing organopolysiloxane to the thermally conductive material by treating the surface of the thermally conductive filler to significantly improve dispersibility (see Patent Documents 12 and 13). However, these treatment agents have the disadvantage of denaturing due to hydrolysis or the like under high temperature and high humidity, thereby inducing performance degradation of the thermally conductive material.

[0012] Prior art literature

[0013] Patent Literature

[0014] Patent Document 1: Japanese Patent Application Laid-Open No. 56-28264

[0015] Patent Document 2: Japanese Patent Application Laid-Open No. 61-157587

[0016] Patent Document 3: Japanese Patent Publication No. 52-33272

[0017] Patent Document 4: Japanese Patent Publication No. 59-52195

[0018] Patent Document 5: Japanese Patent Application Laid-Open No. 2-153995

[0019] Patent Document 6: Japanese Patent Application Laid-Open No. 3-14873

[0020] Patent Document 7: Japanese Patent Application Laid-Open No. 10-110179

[0021] Patent Document 8: Japanese Patent Application Publication No. 2000-63872

[0022] Patent Document 9: Japanese Patent No. 6246986

[0023] Patent Document 10: Japanese Patent Application Publication No. 2002-30217

[0024] Patent Document 11: Japanese Patent Application Publication No. 2000-63873

[0025] Patent Document 12: Japanese Patent Application Publication No. 2004-262972

[0026] Patent Document 13: Japanese Patent Application Publication No. 2005-162975 Summary of the invention

[0027] Problems to be solved by the invention

[0028] The present invention has been made in view of the above-mentioned actual situation, and an object of the present invention is to provide a thermally conductive silicone composition and a method for producing the same, which maintains fluidity and good handling properties even when a high amount of a thermally conductive filler is filled in order to impart excellent insulation and thermal conductivity, and which has excellent heat dissipation performance, durability under high temperature and high temperature and high humidity conditions, and excellent reliability.

[0029] Means for solving problems

[0030] The present inventors have found that by using specific amounts of specific (C) aluminum nitride powder and (D) irregular zinc oxide powder, insulation and high thermal conductivity are achieved while maintaining excellent fluidity, so that handling properties are good, and the composition can follow fine irregularities and reduce contact thermal resistance, thereby obtaining a thermally conductive silicone composition with excellent heat dissipation performance. Furthermore, the composition has excellent durability under high temperature and high temperature and high humidity conditions, and reliability during mounting can be improved, thereby completing the present invention.

[0031] Therefore, the present invention provides the following inventions.

[0032] 1. A thermally conductive silicone composition comprising:

[0033] (A) is represented by the following general formula (1) and has a kinematic viscosity at 25°C of 10 to 10,000 mm 2 / s of organopolysiloxane: 5 to 100 parts by mass,

[0034] [Chemistry 1]

[0035]

[0036] (Where R 1 are independently unsubstituted or substituted monovalent hydrocarbon groups, R 2 are independently alkyl, alkoxyalkyl, alkenyl or acyl, a is an integer of 5 to 100, and b is an integer of 1 to 3.

[0037] (B) represented by the following average composition formula (2) and having a kinematic viscosity at 25°C of 10 to 100,000 mm 2 / s organopolysiloxane: 0 to 95 parts by mass (however, the amount is such that the total amount of the components (A) and (B) is 100 parts by mass.)

[0038] R 3 c SiO (4-c) / 2 (2)

[0039] (Where R 3 are independently unsubstituted or substituted monovalent hydrocarbon groups having 1 to 18 carbon atoms, and c is a number of 1.8 to 2.2.

[0040] (C) Aluminum nitride powder, wherein the oxygen content is 0.5 mass % or less and the BET specific surface area is 1.0 m 2 / g or less, an average particle size of 3 to 40 μm, and a ratio of coarse particles of 44 to 105 μm in a volume-based laser diffraction particle size distribution of 10.0 mass % or less of the total (C) component,

[0041] (D) irregular zinc oxide powder having an average particle size of 0.01 to less than 3.0 μm and a ratio of coarse particles of 25 to 45 μm based on a sieve particle size of 0.2% by mass or less of the total (D) component: the mixing ratio of the component (C) to the component (D) is 5.0:5.0 to 9.5:0.5, and the total powder amount of (C) and (D) is 70 to 85% by volume of the total composition.

[0042] The thermally conductive silicone composition has a thermal conductivity of 4.0 to 9.2 W / m·K in a hot plate method according to ISO 22007-2, and a viscosity at 25° C. of 5 to 800 Pa·s when measured using a spiral viscometer using a rotor A at a rotation speed of 10 rpm.

[0043] 2. The thermally conductive silicone composition according to 1, wherein the component (C) is in the form of round aluminum nitride powder.

[0044] 3. The thermally conductive silicone composition according to 1 or 2, further comprising (E) a volatile solvent for dispersing or dissolving the components (A) and (B): 100 parts by mass or less relative to 100 parts by mass of the total amount of the components (A) and (B).

[0045] 4. The thermally conductive silicone composition according to any one of 1 to 3, further comprising (F) 0.1 to 50 parts by mass of an alkoxysilane represented by the following general formula (3), with which the components (C) and (D) are surface-treated.

[0046] R 4 d R 5 e Si(OR 6 ) 4-d-e (3)

[0047] (Where R 4 are independently an alkyl group having 9 to 15 carbon atoms, R 5 are independently unsubstituted or substituted monovalent hydrocarbon groups having 1 to 8 carbon atoms, R 6 are independently an alkyl group having 1 to 6 carbon atoms, d is an integer of 1 to 3, and e is an integer of 0 to 2, but d+e is an integer of 1 to 3.)

[0048] 5. The thermally conductive silicone composition according to any one of 1 to 4, wherein the viscosity at 25° C. after heat degradation at 200° C. for 100 hours is 1000 Pa·s or less when measured with a spiral viscometer at a rotation speed of 10 rpm.

[0049] 6. The thermally conductive silicone composition according to any one of 1 to 5, wherein after being placed in an atmosphere of 130°C / 85% RH for 96 hours, the thermal resistance at 25°C measured by a laser flash method is 15 mm 2 ·K / W or less.

[0050] 7. The thermally conductive silicone composition according to any one of 1 to 6, wherein the volume resistivity is 10 9 Ω·cm or more.

[0051] 8. A method for producing the thermally conductive silicone composition according to any one of 1 to 7, comprising the step of mixing the components (A) to (D).

[0052] Effects of the Invention

[0053] According to the present invention, a thermally conductive silicone composition and a method for producing the same can be provided. The thermally conductive silicone composition has insulating properties and high thermal conductivity while maintaining excellent fluidity, thereby having good handling properties, excellent heat dissipation performance, excellent durability under high temperature and high temperature and high humidity conditions, and improved reliability during installation. DETAILED DESCRIPTION

[0054] The present invention will be described in detail below. In the present invention, the amount and viscosity expressed as "parts by mass" are values ​​at 25° C. In addition, the "thermal conductive silicone composition" may be simply referred to as "composition".

[0055] [(A) ingredient]

[0056] Component (A) is represented by the following general formula (1):

[0057] [Chemistry 2]

[0058]

[0059] (Where R 1 are independently unsubstituted or substituted monovalent hydrocarbon groups, R 2 are independently alkyl, alkoxyalkyl, alkenyl or acyl, a is an integer of 5 to 100, and b is an integer of 1 to 3. ) represents a kinematic viscosity at 25°C of 10 to 10000 mm 2 / s of organopolysiloxane: 5 to 100 parts by mass.

[0060] The above R 1 Independently unsubstituted or substituted monovalent hydrocarbon groups, for example, straight-chain alkyl groups, branched-chain alkyl groups, cyclic alkyl groups, alkenyl groups, aryl groups, aralkyl groups, and halogenated alkyl groups can be listed. Examples of straight-chain alkyl groups include methyl groups, ethyl groups, propyl groups, hexyl groups, and octyl groups. Examples of branched-chain alkyl groups include isopropyl groups, isobutyl groups, tert-butyl groups, and 2-ethylhexyl groups. Examples of cyclic alkyl groups include cyclopentyl groups and cyclohexyl groups. Examples of alkenyl groups include vinyl groups and allyl groups. Examples of aryl groups include phenyl groups and tolyl groups. Examples of aralkyl groups include 2-phenylethyl groups and 2-methyl-2-phenylethyl groups. Examples of halogenated alkyl groups include 3,3,3-trifluoropropyl groups, 2-(nonafluorobutyl)ethyl groups, and 2-(heptadecafluorooctyl)ethyl groups. Among them, R 1 Preferred are methyl and phenyl.

[0061] The above R 2 are independently alkyl, alkoxyalkyl, alkenyl, or acyl. Examples of the alkyl group include 1The same straight-chain alkyl, branched-chain alkyl, and cyclic alkyl groups as those exemplified above. Examples of alkoxyalkyl groups include methoxyethyl and methoxypropyl. Examples of alkenyl groups include the same groups as those for R 1 The exemplified groups are the same as alkenyl. Examples of acyl groups include acetyl and octanoyl. 2 An alkyl group is preferred, and a methyl group and an ethyl group are more preferred.

[0062] a is an integer of 5 to 100, preferably an integer of 5 to 50, and more preferably an integer of 5 to 30. b is an integer of 1 to 3, and preferably 3.

[0063] The kinematic viscosity of the component (A) at 25°C using an Ostwald viscometer is 10 to 10,000 mm 2 / s, preferably 10~5000mm 2 / s. If the kinematic viscosity is less than 10mm 2 / s, oil bleeds out easily from the obtained thermally conductive silicone composition. On the other hand, if the kinematic viscosity exceeds 10000 mm 2 / s, the fluidity of the obtained thermally conductive silicone composition tends to be poor.

[0064] When the total amount of component (A) and component (B) described later is 100 parts by mass, the amount of component (A) is 5 to 100 parts by mass, preferably 15 to 85 parts by mass, and more preferably 55 to 80 parts by mass. If the amount is within this range, the resulting thermally conductive silicone composition can easily maintain good fluidity and workability, and it is easy to fill the thermally conductive fillers of components (C) and (D) described later in the composition in high amounts. Furthermore, if the amount of component (A) is less than 5 parts by mass, it is sometimes impossible to fill the thermally conductive fillers of components (C) and (D) in high amounts in the thermally conductive silicone composition.

[0065] Preferred specific examples of the component (A) include the following: Me is a methyl group (the same applies hereinafter).

[0066] [Chemistry 3]

[0067]

[0068] [(B) ingredient]

[0069] The component (B) of the present invention is represented by the following average composition formula (2):

[0070] R 3 c SiO (4-c) / 2 (2)

[0071] (Where R 3are independently unsubstituted or substituted monovalent hydrocarbon groups having 1 to 18 carbon atoms, and c is a number of 1.8 to 2.2.

[0072] The kinematic viscosity at 25°C is 10 to 100,000 mm 2 / s of organopolysiloxane. The component (B) is used appropriately for the purpose of imparting properties such as a viscosity modifier and a (pressure-sensitive) adhesiveness imparting agent to the thermally conductive silicone composition of the present invention, but is not limited thereto. The components (B) may be used alone or in combination of two or more.

[0073] The above R 3 R is independently an unsubstituted or substituted monovalent hydrocarbon group having 1 to 18 carbon atoms. 3 , for example, alkyl groups such as methyl, ethyl, propyl, hexyl, octyl, decyl, dodecyl, tetradecyl, hexadecyl, and octadecyl; cycloalkyl groups such as cyclopentyl and cyclohexyl; alkenyl groups such as vinyl and allyl; aryl groups such as phenyl and tolyl; aralkyl groups such as 2-phenylethyl and 2-methyl-2-phenylethyl; halogenated hydrocarbon groups such as 3,3,3-trifluoropropyl, 2-(perfluorobutyl)ethyl, 2-(perfluorooctyl)ethyl, and p-chlorophenyl, etc., and methyl, phenyl, and alkyl groups having 6 to 18 carbon atoms are particularly preferred.

[0074] From the viewpoint of the consistency required for the composition of the present invention as a thermally conductive silicone composition, the above c is a number of 1.8 to 2.2, preferably 1.9 to 2.1.

[0075] The kinematic viscosity of the component (B) at 25°C is 10 to 100,000 mm 2 / s, preferably 10~10000mm 2 / s. If the kinematic viscosity is less than 10mm 2 / s, liquid separation and oil oozing out are likely to occur from the obtained thermally conductive silicone composition. On the other hand, if the kinematic viscosity exceeds 100,000 mm 2 / s, the fluidity of the obtained thermally conductive silicone composition becomes poor, so there is a problem that workability deteriorates.

[0076] Specific examples of the component (B) include:

[0077] [Chemistry 4]

[0078]

[0079] wait.

[0080] When the total amount of component (A) and component (B) is 100 parts by mass, the amount of component (B) is in the range of 0 to 95 parts by mass, that is, including the case where component (B) is not contained. The amount is preferably 15 to 85 parts by mass, more preferably 20 to 45 parts by mass. If the amount is within this range, the composition can easily maintain good fluidity and workability, and it is easy to fill the thermally conductive fillers of components (C) and (D) described later in the composition in high amounts. Furthermore, if the amount of component (B) exceeds 95 parts by mass, it is sometimes not possible to fill the thermally conductive fillers of components (C) and (D) in high amounts in the composition.

[0081] [(C) ingredient]

[0082] The component (C) of the present invention has an oxygen content of 0.5 mass % or less and a BET specific surface area of ​​1.0 m 2 / g or less, an average particle size of 3 to 40 μm, and a ratio of coarse particles of 44 to 105 μm in the volume-based laser diffraction particle size distribution of 10.0 mass % or less of the total (C) component. The (C) component can be used alone or in combination of two or more.

[0083] The oxygen content of component (C) is less than 0.5 mass %, preferably less than 0.2 mass %. There is no particular limitation on the lower limit, and it can be 0.01 mass % or 0 mass %. If the oxygen content, which is an indicator of the nitridation rate of component (C), exceeds 0.5 mass %, the crystallite diameter becomes smaller, and the chemical purity of component (C) deteriorates, so the thermal conductivity of the composition decreases, and sometimes the thermal properties after moisture resistance deteriorate. In addition, with regard to the determination of the oxygen content of component (C), an oxygen-nitrogen analyzer is used for determination, and it can be analyzed by comparison with silicon nitride of standard data. As an oxygen-nitrogen analyzer, "EMGA-920" manufactured by Shimadzu Corporation can be used.

[0084] From the viewpoint of improving the thermal conductivity of the composition, the BET specific surface area (nitrogen adsorption method) of the component (C) is preferably as low as 1.0 m 2 There is no particular restriction on the lower limit of the BET specific surface area, but it can be set to 0.05 m / g based on the upper limit of the average particle size specified in the component (C) and the ratio of the coarse particles specified. 2 The BET specific surface area of ​​the component (C) can be analyzed using, for example, "Macsorb (registered trademark) HM Model-1201" manufactured by Mounttech Co., Ltd.

[0085] The average particle size of the (C) component according to the laser diffraction type particle size distribution (volume basis) is preferably 3 to 40 μm, and more preferably 4 to 40 μm. Furthermore, if the average particle size is less than 3 μm, the filling property in the resin deteriorates, and the viscosity sometimes increases significantly. On the other hand, if the average particle size exceeds 40 μm, it is preferred from the viewpoint of improving the thermal conductivity of the composition, but oil separation may occur easily after a period of time. In addition, the proportion of coarse particles of 44 to 105 μm in the volume-based laser diffraction type particle size distribution is less than 10.0% by mass of the total (C) component, and more preferably less than 8.0% by mass. If the proportion of coarse particles of 44 to 105 μm is less than 10.0% by mass of the total (C) component, the desired thermal resistance and high thermal conductivity can be achieved simultaneously. There is no particular restriction on the lower limit of the proportion of coarse particles of 44 to 105 μm in the laser diffraction type particle size distribution, and it can be made about 0.01% by mass. On the other hand, if the ratio of coarse particles of 44 to 105 μm exceeds 10.0% of the whole, the thickness may not be 44 to 105 μm, and the desired thermal resistance tends to not be achieved.

[0086] As for the component (C), there is no particular limitation as long as the aluminum nitride powder that satisfies the essential characteristics of the present invention can be obtained, and examples thereof include a reduction nitridation method and a direct nitridation method. Among them, from the viewpoint of being easier to obtain an aluminum nitride powder having an oxygen content of 0.5% by mass or less, an aluminum nitride powder obtained by a direct nitridation method is preferred. When obtained by a direct nitridation method, the chemical purity is improved, and thus the thermal characteristics after moisture resistance are further improved.

[0087] The method for producing component (C) can be implemented, for example, by a known direct nitridation method (including combustion synthesis method), and is not particularly limited. For example, a method of nitriding a metal aluminum powder alone in a nitrogen atmosphere of 0.2 to 3 MPa is first listed. It can also be crushed as needed, for example, the crushing method can be implemented by a known method such as a ball mill, a jet mill, a crusher, etc.

[0088] Furthermore, a method including a step of heat treating the component (C) obtained by the direct nitridation method at 1600 to 2000°C in a non-oxidizing atmosphere can be cited. As a result, particles with irregular shapes with edges and corners can be made into round particles with their corners disappeared, which reduces the viscosity of the composition and is therefore suitable. Furthermore, if the temperature is less than 1600°C, it is difficult to make the particles round, and if the temperature exceeds 2000°C, the component (C) is sintered, and the desired average particle size may not be formed.

[0089] The shape of the component (C) may be spherical, polyhedral, or irregular, and is not particularly limited as long as it does not impair the present invention. Among them, a circular shape is preferred from the perspective of reducing the initial viscosity of the composition and reducing the viscosity change during treatment at 200° C., and further improving the heat resistance. It should be noted that in the present invention, the so-called "circular shape" refers to a shape with an aspect ratio of 2.0 or less.

[0090] [(D) ingredient]

[0091] The component (D) is an irregular zinc oxide powder having an average particle size of 0.01 μm or more and less than 3.0 μm, and a ratio of coarse particles of 25 to 45 μm based on a sieve particle size of 0.2 mass % or less of the total component (D), and one kind thereof can be used alone or two or more kinds thereof can be used in combination. The component (D) functions as a thermally conductive filler in the thermally conductive silicone composition of the present invention.

[0092] The average particle size of component (D) is greater than 0.01 μm and less than 3.0 μm, preferably 0.01 to 2.0 μm. If the average particle size of component (D) is within this range, the bulk density of component (D) tends to increase and the specific surface area tends to decrease, so it is easy to fill a high amount of component (D) in the thermally conductive silicone grease composition of the present invention. Furthermore, when the average particle size is smaller than 0.01 μm, the filling property in the resin deteriorates and the viscosity sometimes increases significantly. On the other hand, if the average particle size is too large, greater than 3.0 μm, oil separation may easily occur.

[0093] If the proportion of coarse particles with a sieve size of 25 to 45 μm in the component (D) is less than 0.2% by mass of the whole, the desired thermal resistance and high thermal conductivity can be achieved simultaneously. There is no particular restriction on the lower limit of the proportion of coarse particles with a sieve size of 25 to 45 μm, and it is usually sufficient to be about 0.01% by mass. On the other hand, if the proportion of coarse particles with a sieve size of 25 to 45 μm exceeds 0.2% by mass of the whole, sometimes the thickness of 25 to 45 μm is not achieved, and the desired thermal resistance tends to be unable to be achieved.

[0094] The purity of the component (D) is preferably 99.5% by mass or more, and particularly preferably 99.8% by mass or more from the viewpoint of impurities such as Pb and Cd.

[0095] The shape of the component (D) is preferably an irregular shape, and is not particularly limited, for example, even if it is a spherical shape, a circular shape, a rod shape, a needle shape, or a disc shape, as long as it does not impair the present invention.

[0096] The mixing ratio of component (C) to component (D) is 5.0:5.0 to 9.5:0.5, preferably 6.0:4.0 to 9.0:1.0, expressed as a mass ratio. If the ratio of component (C) is less than 5.0, the filling property of the filler tends to be poor. On the other hand, if the ratio of component (C) exceeds 9.5, it is difficult to fill the filler densely, and the thermal conductivity tends to decrease.

[0097] The total content of the components (C) and (D) in the composition of the present invention is 70 to 85% by volume, preferably 70 to 83% by volume. If the content is less than 70% by volume, the thermal conductivity of the silicone composition may become insufficient, and if it exceeds 85% by volume, it becomes difficult to fill the thermally conductive filler as the components (C) and (D).

[0098] The average particle size of the (C) and (D) components in the present invention is obtained by measuring the volume distribution of the particles using Microtrac (laser diffraction scattering method), multiplying the measured particle size value by the relative particle amount (difference %), and dividing it by the total relative particle amount (100%). Specifically, it can be measured based on volume using the "Laser Diffraction Particle Size Distribution Analyzer SALD-2300" manufactured by Shimadzu Corporation. For the evaluation sample, 50cc of pure water and 5g of the measured thermal conductive powder are added to a glass beaker, stirred with a spatula, and then dispersed for 10 minutes using an ultrasonic cleaner. A solution of the powder of the thermally conductive material that has been dispersed is added drop by drop to the sampler part of the device using a pipette, and waited until it stabilizes until the absorbance can be measured. The measurement is performed at the moment when the absorbance becomes stable. In the laser diffraction particle size distribution analyzer, the particle size distribution is calculated using the data of the light intensity distribution of the diffracted / scattered light generated by the particles detected by the sensor. The average particle size is obtained by multiplying the measured particle size by the relative particle amount (difference %) and dividing the result by the total relative particle amount (100%). The average particle size is the average diameter of the particles. In addition, the proportion of coarse particles of 44 to 105 μm in the component (C) can also be easily confirmed from the overall particle size distribution.

[0099] [(E) ingredient]

[0100] In the composition of the present invention, a volatile solvent that disperses or dissolves the components (A) and (B) may be added as the component (E). In the case where the composition of the present invention further comprises the component (F) described below in addition to the components (A) and (B), it is preferred that the volatile solvent that can also disperse or dissolve the component (F) is used. The component (E) may be any solvent as long as it can dissolve or disperse the components (A) and (B) and the component (F) that is sometimes used. The component (E) may be used alone or in combination of two or more.

[0101] The thermal conductivity of a thermally conductive silicone composition is basically related to the filling rate of the thermally conductive filler, so the more the thermally conductive filler is filled, the higher the thermal conductivity. However, of course, if the filling amount of the thermally conductive filler is increased, the viscosity of the thermally conductive silicone composition itself is likely to increase, and the expansion of the composition when a shearing action is applied is also likely to increase. In particular, in screen printing, when the thermally conductive silicone composition is extruded, if the expansion in the thermally conductive silicone composition is strongly manifested, the fluidity of the thermally conductive silicone composition is temporarily strongly suppressed, so that the thermally conductive silicone composition cannot pass through the screen mask and the screen mesh, and sometimes the coating property is extremely deteriorated. As a result, in the past, it was difficult to easily and uniformly apply a high thermally conductive silicone composition filled with a high amount of thermally conductive filler to a heat sink or the like using screen printing. Even if the thermally conductive silicone composition of the present invention contains the thermally conductive fillers (C) and (D) at a high filling rate, when the volatile solvent (E) is contained, the viscosity tends to drop sharply and the expansion is not easy to appear, so the coating property tends to be good, and it can be easily applied to a heat sink or the like by screen printing. After coating, the contained component (E) is easily volatilized at room temperature or actively heated. Therefore, according to the present invention, the highly thermally conductive silicone composition filled with a high amount of thermally conductive filler can be easily and uniformly thinly placed on a heat sink or the like by screen printing.

[0102] The boiling point of the component (E) is preferably within the range of 80 to 260° C. If the boiling point is within this range, it is easy to prevent the component (E) from volatilizing rapidly from the composition during the coating operation of the obtained composition, thereby easily suppressing the increase in the viscosity of the composition and easily ensuring the coating properties of the composition. In addition, after the coating operation of the composition, the component (E) is unlikely to remain in the composition, so the heat dissipation characteristics are easily improved.

[0103] Specific examples of the component (E) include toluene, xylene, acetone, methyl ethyl ketone, cyclohexane, n-hexane, n-heptane, butanol, isopropyl alcohol (IPA), and isoparaffin solvents. Among them, isoparaffin solvents are preferred from the perspectives of safety, health, and workability, and isoparaffin solvents having a boiling point of 80 to 260° C. are particularly preferred.

[0104] When the component (E) is added to the composition of the present invention, the amount thereof is preferably 100 parts by mass or less, more preferably 75 parts by mass or less, relative to 100 parts by mass of the components (A) and (B). If the amount is within this range, it is easy to suppress the rapid precipitation of the components (C) and (D), so that the storage stability of the composition is easily improved.

[0105] [(F)INGREDIENT]

[0106] Component (F) is represented by the following general formula (3):

[0107] R 4 d R 5 e Si(OR 6 ) 4-d-e (3)

[0108] (Where R 4 are independently an alkyl group having 9 to 15 carbon atoms, R 5 are independently unsubstituted or substituted monovalent hydrocarbon groups having 1 to 8 carbon atoms, R 6 Each of the alkyl groups is independently an alkyl group having 1 to 6 carbon atoms, d is an integer of 1 to 3, and e is an integer of 0 to 2, but d+e is an integer of 1 to 3. ) is an alkoxysilane represented by

[0109] Component (F) is a wetting agent component and is also an additive to prevent component (A) from denaturing under high temperature and high humidity. By treating the surface of the thermally conductive filler of component (C) and component (D) with component (F), the wettability of component (A) to component (C) and component (D) can also be improved. As a result, component (F) assists in the high-volume filling of component (C) and component (D). In addition, by using component (F) together with component (A), it acts to inhibit the contact between water vapor and component (A) under high temperature and high humidity. As a result, component (F) prevents the denaturation of component (A) caused by hydrolysis under high temperature and high humidity conditions, which deteriorates the performance of the thermally conductive silicone composition of the present invention. Component (F) can be used alone or in combination of two or more.

[0110] The above R 4 The alkyl group is independently an alkyl group having 9 to 15 carbon atoms, and specific examples thereof include nonyl, decyl, dodecyl, tetradecyl, pentadecyl, etc., and decyl is particularly preferred. If the number of carbon atoms is less than 9, wettability with the thermally conductive filler (component (C) and component (D)) is likely to become insufficient, and if it exceeds 15, component (F) is likely to solidify at room temperature, so that its handling is likely to become inconvenient, and the heat resistance and flame retardancy of the obtained composition are likely to be reduced.

[0111] The above R 5 It is independently an unsubstituted or substituted saturated or unsaturated monovalent hydrocarbon group having 1 to 8 carbon atoms. Specific examples thereof include alkyl groups such as methyl, ethyl, propyl, hexyl, and octyl; cycloalkyl groups such as cyclopentyl and cyclohexyl; alkenyl groups such as vinyl and allyl; aryl groups such as phenyl and tolyl; aralkyl groups such as 2-phenylethyl and 2-methyl-2-phenylethyl; halogenated hydrocarbon groups such as 3,3,3-trifluoropropyl, 2-(nonafluorobutyl)ethyl, and p-chlorophenyl, and methyl, ethyl, and vinyl are particularly preferred.

[0112] The above R 6Specific examples of the alkyl group independently having 1 to 6 carbon atoms include methyl, ethyl, propyl, butyl, pentyl, and hexyl. A methyl group and an ethyl group are particularly preferred.

[0113] The above d is usually an integer of 1-3, and particularly preferably 1. The above e is an integer of 0-2. However, d+e is an integer of 1-3.

[0114] As specific examples of the component (F), the following examples can be mentioned, for example.

[0115] C 10 H 21 Si(OCH3)3,

[0116] C 12 H 25 Si(OCH3)3,

[0117] C 12 H 25 Si(OC2H5)3,

[0118] C 10 H 21 Si(CH3)(OCH3)2,

[0119] C 10 H 21 Si(C6H5)(OCH3)2,

[0120] C 10 H 21 Si(CH3)(OC2H5)2,

[0121] C 10 H 21 Si(CH=CH2)(OCH3)2,

[0122] C 10 H 21 Si(CH2CH2CF3)(OCH3)2

[0123] The amount of component (F) is preferably 0.1 to 50 parts by mass, and more preferably 1 to 20 parts by mass, relative to 100 parts by mass of the total of components (A) and (B). If the amount is within this range, the wetting agent effect and the high temperature and high humidity resistance effect are easily increased according to the amount added, which is economical. On the other hand, since component (F) is slightly volatile, if the thermally conductive silicone composition containing component (F) is placed in an open system, component (F) sometimes evaporates from the composition and the composition slowly hardens. However, if the amount added is within this range, such a phenomenon can be easily prevented.

[0124] [Other additives]

[0125] In the composition of the present invention, commonly used additives or fillers can be further added as optional components within the scope of not impairing the purpose of the present invention. Specifically, fluorine-modified silicone surfactants; carbon black, titanium dioxide, red iron oxide, etc. as colorants; platinum catalysts, metal oxides such as iron oxide, titanium oxide, cerium oxide, or metal hydroxides as flame retardant imparting agents can be added. Furthermore, fine powdered silica such as precipitated silica or calcined silica, thixotropy enhancers, etc. can also be optionally added as anti-precipitation agents for thermal conductive fillers at high temperatures. In addition, the blending amount when such optional components are combined can be set to less than 1% by mass in the thermally conductive silicone composition, preferably less than 0.5% by mass.

[0126] [Manufacturing method]

[0127] The composition of the present invention is prepared by mixing components (A) to (D) and the above optional components. Examples of mixers include mixing equipment such as a gate mixer (kneader), a frame mixer, and a planetary mixer. The composition has greatly improved thermal conductivity and good workability, durability, and reliability.

[0128] [Thermal conductive silicone composition]

[0129] [Thermal conductivity]

[0130] The thermal conductivity of the composition of the present invention at 25°C is 4.0 to 9.2 W / m·K, preferably 5.0 to 9.2, in the hot plate method according to ISO 22007-2. Such thermal conductivity is obtained according to the composition of the present invention. The thermal conductivity of the composition of the present invention can be measured, for example, using the trade name "TPS2500S" manufactured by Kyoto Electronics Co., Ltd.

[0131] [Viscosity]

[0132] In addition, the viscosity of the composition of the present invention at 25°C is 5 to 800 Pa·s, preferably 5 to 500 Pa·s, when measured at a rotation speed of 10 rpm using a spiral viscometer using rotor A. If the viscosity is within this range, the fluidity of the obtained composition is easy to become good, so the workability such as dispensability and screen printing is easy to improve, and it is easy to apply the composition thinly to the substrate. In addition, after thermal degradation at 200°C × 100 hours, the viscosity at 25°C is preferably less than 1000 Pa·s, more preferably less than 800 Pa·s, and further preferably less than 400 Pa·s when measured at a rotation speed of 10 rpm using a spiral viscometer. Such a non-curing liquid is preferred. It should be noted that in the measurement of viscosity, a spiral viscometer using rotor A is used when the rotation speed is 10 rpm. As an apparatus, for example, a spiral viscometer with the trade name "PC-10AA type" manufactured by Malcom Company Limited can be used for measurement.

[0133] [Thermal resistance]

[0134] The composition of the present invention preferably has a thermal resistance of 15 mm at 25°C after being placed in an atmosphere of 130°C / 85% RH for 96 hours using a laser flash method. 2 · K / W or less, preferably 12mm 2 · K / W or less. If the thermal resistance is within this range, even when the composition of the present invention is applied to a heating element with a large calorific value, the heat generated from the heating element can be efficiently dissipated to the heat dissipation component. It should be noted that the measurement of thermal resistance using the laser flash method can be performed in accordance with ASTM E 1461.

[0135] [Volume resistivity]

[0136] The volume resistivity of the composition of the present invention is preferably 10 9 Ω·cm or more, more preferably 10 10 Ω·cm or more. There is no particular upper limit, but it can be 10 16 Ω·cm or less. The volume resistivity can be measured in accordance with JIS K 6911. The details are the method described in the Examples.

[0137] [Use of the composition]

[0138] The thermally conductive silicone composition of the present invention is applied to a heating element or a heat sink. Examples of the heating element include general power supplies; electronic devices such as power transistors, power modules, thermistors, thermocouples, and temperature sensors for power supplies; heat-generating electronic components such as integrated circuit elements such as LSIs and CPUs; and the like. Examples of the heat sink include heat sinks and other heat dissipating components; heat pipes, heat sinks, and the like. Application can be performed, for example, by screen printing. Screen printing can be performed, for example, using a metal mask or a silk screen. By applying the composition of the present invention between the heating element and the heat sink, heat can be efficiently conducted from the heating element to the heat sink, thereby effectively removing heat from the heating element.

[0139] The thermally conductive silicone composition of the present invention has insulating properties and good thermal conductivity, and furthermore, since it maintains good fluidity, it has excellent workability. In addition, since it also has excellent adhesion to heat-generating electronic components and heat-dissipating components, by placing the thermally conductive silicone composition of the present invention between the heat-generating electronic components and the heat-dissipating components, the heat generated from the heat-generating electronic components can be efficiently dissipated to the heat-dissipating components. Furthermore, the thermally conductive silicone composition of the present invention also has excellent durability under high temperatures and high temperatures and high humidity. For example, when used in heat dissipation of general power supplies, electronic devices, etc., and heat dissipation of integrated circuit components such as LSI and CPU used in electronic devices such as personal computers and DVD drives, it can provide very good reliability. The use of the thermally conductive silicone composition of the present invention can greatly improve the stability and life of heat-generating electronic components, electronic devices using the same, etc.

[0140] Example

[0141] The following examples and comparative examples are shown to specifically illustrate the present invention, but the present invention is not limited to the following examples. In addition, in the following examples, unless otherwise specified, the "%" of the composition represents mass %, the ratio represents mass ratio, and the amount of each component in the table is the amount converted by purity.

[0142] The components used in the composition of the present invention are as follows.

[0143] (A) Organopolysiloxane having an alkoxy group bonded to a silicon atom

[0144] A-1: The kinematic viscosity represented by the following formula is 35 mm 2 / s organic polysiloxane

[0145] [Chemistry 5]

[0146]

[0147] (B) Organopolysiloxane

[0148] B-1: The kinematic viscosity represented by the following formula is 500 mm 2 / s organic polysiloxane

[0149] [Chemistry 6]

[0150]

[0151] (C) Aluminum nitride powder

[0152] [Table 1]

[0153]

[0154] The average particle size shown in Table 1 is calculated from the average particle size distribution obtained in the laser diffraction type particle size distribution by the method for measuring the average particle size of the components (C) and (D) in the present invention. In addition, the coarse particle content is the ratio of coarse particles of 44 to 105 μm relative to the overall particle size distribution obtained in the laser diffraction type particle size distribution. In addition, the round (C) component is obtained by heat treating the (C) component obtained by the direct nitridation method at 1750°C in a non-oxidizing atmosphere.

[0155] (D) Zinc oxide powder (average particle size 0.27 μm, coarse particle content in the undersize fraction with a mesh size of 45 μm specified in JIS Z 8801-1 is 0.0%)

[0156] The average particle size shown here is calculated from the entire particle size distribution obtained in the laser diffraction type particle size distribution. The coarse particle content depends on the sieve particle size, and the ratio of coarse particles of 25 to 45 μm to the entire particle size distribution obtained in the laser diffraction type particle size distribution is also the same.

[0157] (E) a volatile solvent capable of dispersing or dissolving components A-1, B-1, and F-1

[0158] E-1: Isosol (registered trademark) 400 (trade name, isoparaffin solvent, boiling point: 210-254° C., manufactured by Nippon Petrochemical Corporation)

[0159] (F) Alkoxysilane

[0160] F-1: Alkoxysilane represented by the following formula

[0161] C 10 H 21 Si(OCH3)3

[0162] [Examples, Comparative Examples]

[0163] [Manufacturing method]

[0164] Components (A) to (F) are mixed as described below to obtain compositions of Examples and Comparative Examples. Specifically, components (A) to (D) are measured in a 5-liter planetary mixer (manufactured by Inoue Manufacturing Co., Ltd.) at the composition ratios (parts by mass) shown in Tables 2 and 3, and mixed under reduced pressure at 150°C for 1 hour and under conditions of less than 30 mmHg. Then, the obtained mixture is cooled to room temperature and mixed. When components (E) and (F) are added, components (E) and (F) are added to the cooled mixture in the amounts shown in Tables 2 and 3, and mixed to make it uniform. The properties of the obtained compositions are determined by the following test methods. The results are collectively recorded in Tables 2 and 3.

[0165] [Viscosity measurement]

[0166] The obtained composition was left in a thermostatic chamber at 25° C. for 24 hours, and then the viscosity was measured at a rotation speed of 10 rpm using a viscometer (trade name: Spiral Viscometer PC-10AA, manufactured by Malcom Co., Ltd.) using an A-type rotor.

[0167] [Viscosity measurement after thermal degradation]

[0168] The obtained composition was thermally degraded at 200° C. for 100 hours using a dryer, and then allowed to stand in a constant temperature chamber at 25° C. for 24 hours, and then measured in the same manner as above.

[0169] [Thermal conductivity measurement]

[0170] Two samples of the obtained composition were wrapped with kitchen wrap to prevent bubbles from entering, and the samples were sandwiched between a sensor of a thermal conductivity meter (trade name: TPS-2500S) manufactured by Kyoto Electronics Co., Ltd. to measure the thermal conductivity of the composition at 25°C.

[0171] [Preparation of test pieces for thickness and thermal resistance measurement]

[0172] A composition having a thickness of 75 μm was sandwiched between two circular aluminum plates having a diameter of 12.6 mm and a thickness of 1 mm, and a pressure of 0.15 MPa was applied at 25° C. for 60 minutes to prepare a test piece.

[0173] [Thickness measurement]

[0174] The thickness of the test piece was measured using a micrometer (manufactured by Mitutoyo Corp.), and the thickness of the composition was calculated by subtracting the thickness of two aluminum plates measured in advance.

[0175] [Measurement of thermal resistance]

[0176] The thermal resistance (unit: mm) of the composition was measured at 25° C. using the test piece using a thermal resistance measuring instrument based on the laser flash method (manufactured by Netch Co., Ltd., xenon flash analyzer; LFA447 NanoFlash). 2 ·K / W).

[0177] [Measurement of thermal resistance after storage under high temperature and high humidity]

[0178] After the thermal resistance measurement, the test piece was left in an atmosphere of 130°C / 85% RH for 96 hours, and the thermal resistance (unit: mm) of the composition was measured again at 25°C using the thermal resistance measuring instrument. 2 ·K / W).

[0179] [Measurement of volume resistivity]

[0180] In order to measure by the double ring electrode method based on JIS K 6911, a test piece was prepared so that the sample thickness would be 1.0 mm, 500 V was applied between the electrodes, and the volume resistivity was measured after 1 minute.

[0181] [Table 2]

[0182]

[0183] E+10 means ×10 10 .

[0184] [Table 3]

[0185]

[0186] *Cannot be measured due to failure to mix, E+10 means ×10 10 .

Claims

1. A thermally conductive silicone composition comprising: (A) is represented by the following general formula (1) and has a kinematic viscosity at 25°C of 10 to 10,000 mm 2 / s of organopolysiloxane: 5 to 100 parts by mass, [Chemistry 1] In the formula, R 1 are independently unsubstituted or substituted monovalent hydrocarbon groups, R 2 are independently alkyl, alkoxyalkyl, alkenyl or acyl, a is an integer of 5 to 100, b is an integer of 1 to 3, (B) represented by the following average composition formula (2) and having a kinematic viscosity at 25°C of 10 to 100,000 mm 2 / s of organopolysiloxane: 0 to 95 parts by mass, and such an amount that the total amount of the component (A) and the component (B) is 100 parts by mass, R 3 c SiO (4-c) / 2 (2) In the formula, R 3 are independently unsubstituted or substituted monovalent hydrocarbon groups having 1 to 18 carbon atoms, c is a number from 1.8 to 2.2, (C) Aluminum nitride powder, wherein The oxygen content is less than 0.5 mass % and the BET specific surface area is 1.0 m 2 / g or less, an average particle size of 3 to 40 μm, and a ratio of coarse particles of 44 to 105 μm in a volume-based laser diffraction particle size distribution of 10.0 mass % or less of the entire component (C), (D) irregular zinc oxide powder having an average particle size of 0.01 μm or more and less than 3.0 μm, and a ratio of coarse particles of 25 to 45 μm based on a sieve particle size of 0.2 mass % or less of the total (D) component: the mixing ratio of the (C) component to the (D) component is 5.0:5.0 to 9.5:0.5, and the total powder amount of (C) and (D) is 70 to 85% by volume of the entire composition. The thermally conductive silicone composition has a thermal conductivity of 4.0 to 9.2 W / m·K in a hot plate method according to ISO 22007-2, and a viscosity at 25° C. of 5 to 800 Pa·s when measured using a spiral viscometer using a rotor A at a rotation speed of 10 rpm.

2. The thermally conductive silicone composition according to claim 1, wherein The shape of the component (C) is round aluminum nitride powder.

3. The thermally conductive silicone composition according to claim 1, further comprising (E) a volatile solvent for dispersing or dissolving the components (A) and (B): 100 parts by mass or less based on 100 parts by mass of the total amount of the components (A) and (B).

4. The thermally conductive silicone composition according to claim 1, further comprising (F) 0.1 to 50 parts by mass of an alkoxysilane represented by the following general formula (3), with which components (C) and (D) are surface-treated. R 4 d R 5 e Si(OR 6 ) 4-d-e (3) In the formula, R 4 are independently an alkyl group having 9 to 15 carbon atoms, R 5 are independently unsubstituted or substituted monovalent hydrocarbon groups having 1 to 8 carbon atoms, R 6 Each of the groups is independently an alkyl group having 1 to 6 carbon atoms, d is an integer of 1 to 3, and e is an integer of 0 to 2, but d+e is an integer of 1 to 3. 5 . The thermally conductive silicone composition according to claim 1 , wherein after heat degradation at 200° C. for 100 hours, the viscosity at 25° C. is 1000 Pa·s or less when measured with a spiral viscometer at a rotation speed of 10 rpm.

6. The thermally conductive silicone composition according to claim 1, wherein after being placed in an atmosphere of 130°C / 85% RH for 96 hours, the thermal resistance at 25°C measured by a laser flash method is 15 mm 2 ·K / W or less.

7. The thermally conductive silicone composition according to claim 1, wherein the volume resistivity is 10 9 Ω·cm or more. 8 . A method for producing the thermally conductive silicone composition according to claim 1 , comprising the step of mixing the components (A) to (D).

Citation Information

Patent Citations

  • Shirikoonguriisusoseibutsu

    JP1977033272B2

  • Thixotropic heat conductive material

    JP1981028264A

  • The thermally conductive silicone composition - amine

    JP1984052195B2

  • Acid-resistant heat-dissipating grease

    JP1986157587A

  • Aluminum nitride substrate and manufacture

    JP1987046986A

Cited By

  • Zinc oxide ceramic with adjustable nonlinear coefficient as well as preparation method and application of zinc oxide ceramic

    CN118084479A